Using Ultrasound-Based Multilayer Perceptron to Differentiate Early Breast Mucinous Cancer and its Subtypes From Fibroadenoma - Liang, Ting; Shen, Junhui; Zhang, Shumei; Cong, Shuzhen; Liu, Juanjuan; Pei, Shufang; Shang, Shiyao; Huang, Chunwang (Frontiers in Oncology, 2021)
Objectives Mucinous breast cancer (MBC), particularly pure MBC (pMBC), often tend to be confused with fibroadenoma (FA) due to their similar images, and firm masses, so some MBC cases mis-diagnosed to be FA may cause poor prognosis. We analyzed the ultrasonic features and aimed to identify the ability of multilayer perceptron (MLP) to classify early MBC and its subtypes and FA. Materials and Methods The study consisted of 193 patients diagnosed with pMBC, mMBC or FA. The area under curve (AUC) was calculated to assess the effectiveness of age and 10 ultrasound features in differentiating MBC from FA. We used the pairwise comparison to examine the differences among MBC subtypes (pure and mixed types) and FA. We utilized the MLP to differentiating MBC and its subtypes from FA. Results The 9 features with AUCs over 0.5 were as follows: age, echo pattern, shape, orientation, margin, echo rim, vascularity distribution, vascularity grade and tumor size. In subtype analysis, the significant differences were obtained in 10 variables (P-value range: 0.000-0.037) among pMBC, mMBC and FA, except posterior feature. Through MLP, the AUCs of predicting MBC and FA were both 0.919; the AUCs of predicting pMBC, mMBC and FA were 0.875, 0.767, and 0.927, respectively. Conclusion Our study found that the MLP models based on ultrasonic characteristics and age can well distinguish MBC and its subtypes from FA. It may provide a critical insight into MBC preoperative clinical management.